Retinal vasoproliferative tumors: Comparative clinical features of primary vs secondary tumors in 334 cases - Carol L. Shields (2018)
Objective: To compare the clinical features of primary vs secondary retinal vasoproliferative tumors (VPTs). Methods: Retrospective case series of 334 tumors in 295 eyes of 275 patients. Results: Of 275 patients with VPT, 41% (n=113) were male and 59% (n=162) were female, with a mean age of 44 years at presentation. Primary VPT occurred in 80% (n=219) and secondary VPT, in 20% (n=56) of patients. Secondary VPT (n=67) occurred in eyes with retinitis pigmentosa (n=15, 22%), pars planitis (n=14, 21%), Coats disease (n=11, 16%), previous retinal detachment surgery (n=8, 12%), idiopathic peripheral retinal vasculitis (n=4, 6%), familial exudative vitreoretinopathy (n=3, 4%), and others (n=12, 18%). The mean interval between diagnosis of underlying ocular condition and secondary VPT was 160 months. Statistically significant differences (P<.05) in clinical features (primary vs secondary VPTs) included mean age at presentation (46 vs 38 years), visual symptoms (74% vs 87%), poor visual acuity worse than 20/200 (15% vs 28%), bilaterality (4% vs 20%), multifocality (5% vs 15%), postequatorial tumor location (20% vs 33%), tumor basal dimension (6 vs 7 mm), anterior chamber cells (16% vs 30%), and vitreous cells (19% vs 48%). Conclusions: Retinal vasoproliferative tumor can be primary (80%) or secondary (20%). Compared with primary VPT, secondary VPT is more often bilateral, multiple, and larger and occurs at an earlier age associated with poorer visual acuity. © 2013 American Medical Association. All rights reserved.